Relationship of TTF-1 and EGFR on Lung Adenocarcinoma at Dr. Saiful Anwar General Hospital Malang - lumban gaol, andy; Pratiwi, Suryanti Dwi; Putra, Ngakan Putu; Norahmawati, Eviana; Rasyid, Harun Al (Jurnal Kedokteran Brawijaya, 2020)
There is a correlation between mutation of Epidermal Growth Factor Receptor (EGFR) and lung adenocarcinoma. Unfortunately, examination for EGFR mutation is difficult because surgery must be conducted to obtain the best specimen. Thyroid Transcription Factor-1 (TTF-1) is a marker for lung adenocarcinoma. This observational study took place at Dr. Saiful Anwar Hospital from stored biological materials from 2013-2018. Samples were lung adenocarcinoma patients that undergo EGFR examination. Data then analyzed using Fischer's Exact Test to determine the relationship between EGFR and TTF-1. Specificity/sensitivity value is 0.75/0.90, p: 0.617, odds ratio 0.333 (0.032-3.515). However, Receiver Operating Characteristic (ROC) curve of TTF- 1 show AUC 0.614 (95CI, 0.35- 0.878). TTF-1 examination has a moderate strength in determining EGFR mutation on lung adenocarcinoma patients at Dr. Saiful Anwar Hospital.